Chitosan pH Sensor - Irwana, Nainggolan, Dr.; Khairel Rafezi, Ahmad, Dr.; Ainnie Shakirah, Arif (Malaysian Invention and Design Society (MINDS), 2010)
Dr. Irwana Nainggolan and her team won silver at 21st International Invention, Innovation and Technology Exhibition (ITEX) 2010, 14th - 16th May 2010 di Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur, Malaysia.